2020
DOI: 10.1016/j.jstrokecerebrovasdis.2020.104867
|View full text |Cite
|
Sign up to set email alerts
|

A novel model for predicting the outcome of intracerebral hemorrhage: Based on 1186 Patients

Abstract: Objective: To establish a model for predicting the outcome according to the clinical and computed tomography(CT) image data of patients with intracerebral hemorrhage(ICH). Methods: The clinical and CT image data of the patients with ICH in Qinghai Provincial People's Hospital and Xuzhou Central Hospital were collected. The risk factors related to the poor outcome of the patients were determined by univariate and multivariate logistic regression analysis. To determine the effect of factors related to poor outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
(11 reference statements)
2
6
0
Order By: Relevance
“…Similar to many previous studies, we found that age ( Inoue et al, 2018 ; He et al, 2020 ), GCS score ( Cui et al, 2020 ), and bleeding volume ( Al-Shahi Salman et al, 2018 ; Du et al, 2020 ; He et al, 2020 ; Kang et al, 2021 ; Masotti et al, 2021 ; Pasi et al, 2021 ) were independent risk factors for the poor prognosis of ICH patients. It is generally believed that the main causes of ICH are hypertension and CAA ( Schrag and Kirshner, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar to many previous studies, we found that age ( Inoue et al, 2018 ; He et al, 2020 ), GCS score ( Cui et al, 2020 ), and bleeding volume ( Al-Shahi Salman et al, 2018 ; Du et al, 2020 ; He et al, 2020 ; Kang et al, 2021 ; Masotti et al, 2021 ; Pasi et al, 2021 ) were independent risk factors for the poor prognosis of ICH patients. It is generally believed that the main causes of ICH are hypertension and CAA ( Schrag and Kirshner, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…These data indicate that the constructed model can reduce the number of variables and its predictive performance is not worse than that of commonly used scoring systems. Similar to many previous studies, we found that age (Inoue et al, 2018;He et al, 2020), GCS score (Cui et al, 2020), and bleeding volume (Al-Shahi Salman et al, 2018;Du et al, 2020;FIGURE 3 Thirty-day mortality nomogram for intracerebral hemorrhage. Nomogram included age, GCS, creatinine, WBC, temperature, glucose, urine output, and bleeding volume for predicting 30-day mortality after an acute intracerebral hemorrhage.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Baseline hematoma volume (> 20 ml), IVH, age (> 53 years), and diabetes had the highest percentage of influence weight in a ML model developed by He and colleagues [ 18 ] to estimate poor outcome in supratentorial spontaneous ICH treated with conservative treatment. Another ML-based radiomics-clinical model constructed to predict IVH growth after spontaneous ICH found as independent predictors of IVH growth: hypercholesterolemia, baseline Graeb score, time to initial CT, international normalized ratio, and Rad score [ 43 ].…”
Section: Discussionmentioning
confidence: 99%